Exploring Indonesian Celebrity Controversial Issues and Hate Speech in Social Media - Afifah, Wiwiek; Windarti, Ani; Budiwati, Tri Rina (PAROLE: Journal of Linguistics and Education, 2024)
The purpose of this study is to explore the interplay between Indonesian celebrity’s controversial issues and the responses of haters as seen in the on-line hate speech. To have a better understanding of the controversies, a case study was applied, in the meantime, the issue of hate speech was viewed from content analysis. The data concerning the celebrity’s life were taken from both printed and on-line media; meanwhile, the ones relating to hate speech were gathered from two mainstream social media platforms: Instagram and Twitter spanning from 2015 to 2022. The results of the study indicate that there are three controversial issues which might bring about hate speech: celebrity’s past controversial marriage life, the status as a divorcee who often changes boyfriends, and the family’s controversies. In addition, haters’ reaction toward those controversial issues were expressed through swearing, the use of euphemism and dysphemism consisting of social, personality, religious insults, satanic expression, provocations, mockery, anger expressions written with capital letters, and accusation for blowing up the reputation relating to family. The hate speech expressed by Indonesian netizens is in serious condition and can influence other aspect of life in society.